2016
DOI: 10.1371/journal.pone.0163142
|View full text |Cite
|
Sign up to set email alerts
|

Complex Interplay between FleQ, Cyclic Diguanylate and Multiple σ Factors Coordinately Regulates Flagellar Motility and Biofilm Development in Pseudomonas putida

Abstract: Most bacteria alternate between a free living planktonic lifestyle and the formation of structured surface-associated communities named biofilms. The transition between these two lifestyles requires a precise and timely regulation of the factors involved in each of the stages that has been likened to a developmental process. Here we characterize the involvement of the transcriptional regulator FleQ and the second messenger cyclic diguanylate in the coordinate regulation of multiple functions related to motilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
83
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(87 citation statements)
references
References 83 publications
(112 reference statements)
4
83
0
Order By: Relevance
“…A recent study by Jiménez‐Fernández and colleagues () has confirmed that FleQ positively regulates the expression of flagella‐associated genes in P. putida . Here, in P. putita KT2440, we found that deletion of fleN led to increased flagellar number (Fig.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…A recent study by Jiménez‐Fernández and colleagues () has confirmed that FleQ positively regulates the expression of flagella‐associated genes in P. putida . Here, in P. putita KT2440, we found that deletion of fleN led to increased flagellar number (Fig.…”
Section: Resultsmentioning
confidence: 82%
“…Previous report from P. aeruginosa showed that FleN exerted an antagonistic effect on FleQ in flagella biosynthesis through inhibiting FleQ ATPase activity (Baraquet and Harwood, ), while FleQ ATPase activity and RpoN were not required for biofilm gene expression (Baraquet and Harwood, ), suggesting a different regulation mechanism between the flagella synthesis and biofilm formation in P. aeruginosa . Unlike FleQ in P. aeruginosa , FleQ of P. putida functioned as an activator for both flagella‐related genes and biofilm‐related gene lapA (Jiménez‐Fernández et al ., ; Xiao et al ., ). In addition, we discovered that ATPase of FleQ and RpoN were required for full expression of lapA and were strictly needed for the expression of fleSR and fliF (Xiao et al ., ), suggesting that FleQ probably relies on σ 54 to regulate lapA expression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, cdGMP binding to FleQ antagonizes its repressor activity, thereby enabling transcription from the same promoter it was otherwise inhibiting. This TF is so important in lifestyle decisions that a P. putida strain lacking fleQ is both non-motile and unable to form biofilms (Jimenez-Fernandez et al, 2016;Molina-Henares et al, 2017). FleQ can also interact with another TF, FleN.…”
Section: Introductionmentioning
confidence: 99%
“…Flagellum-dependent swimming motility, for example, is controlled through a regulatory cascade that includes the transcriptional regulator, FleQ (3) and the FleS-FleR TCS, which like many TCSs also requires the alternate sigma factor RpoN (σ 54 )(4). FleQ controls transcription of fleS-fleR in addition to multiple other flagellar, adhesion and biofilm-associated genes, in a c-di-GMP dependent manner (3,5). FleSR has been implicated in the expression of 20 or more flagellar biosynthetic genes in P. aeruginosa , as well as additional genes not previously known to be involved in flagellar assembly or function (6).…”
Section: Introductionmentioning
confidence: 99%